Penetrating pulmonary vein laceration following blunt chest trauma. (February 2022) - Ishay, Shlomo Y.; Raichel, Lior; Tabo, Limor Y.; Semyonov, Michael; Barsky, Guy; Acker, Asaf; Shaked, Gad; Sahar, Gideon
Abstract: Flail chest is a common injury in blunt trauma which is usually treated with analgesia, oxygen, and other conservative measures. In more severe cases mechanical ventilation and surgical stabilization of rib fractures (SSRF) may be warranted. Penetrating injury to the heart or great vessels due to rib fractures however, is much less common. Here we present a 33 year old male that was admitted to the Emergency department (ED) after a horse riding accident, demonstrating severe shock. Emergency computerized tomography scan showed multiple bilateral displaced rib fractures, Left hemothorax and possibly a penetrating injury to the left side of the heart by one of the ribs. Notably, no significant pericardial effusion was demonstrated. In addition, a grade V splenic injury was diagnosed. A Joined thoracic and abdominal emergent surgical treatment was successfully carried out and the patient survived and fully recovered.